Pengaruh Kompensasi, Kekayaan Partner, dan Moral terhadap Kualitas Audit dengan Moderasi Skeptisisme - Mutia Kholisah; Imam Hidayat (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the influence of fee-based compensation, partner net worth, and moral reasoning on audit quality in infrastructure companies listed on the Indonesia Stock Exchange during the 2021–2025 period. The population consists of all infrastructure sector companies, and purposive sampling was applied to select 18 companies, resulting in 90 firm-year observations. Secondary data were obtained from published annual reports. Data analysis employed multiple linear regression and Moderated Regression Analysis (MRA) to evaluate the moderating role of professional skepticism. Audit quality was proxied by Audit Report Lag. The results indicate that fee-based compensation, partner net worth, and moral reasoning, both partially and simultaneously, do not have a significant effect on audit quality. In addition, professional skepticism does not moderate the relationship between the independent variables and audit quality. These findings imply that audit timeliness in capital-intensive infrastructure companies is more likely influenced by operational complexity than by economic incentives or ethical considerations of auditors. This research contributes by integrating economic incentive theory and ethical decision-making perspectives within a comprehensive empirical model during a period of economic uncertainty, providing implications for regulators in assessing audit fee standards and reporting efficiency in Indonesia.